2021
DOI: 10.1111/bcp.15072
|View full text |Cite
|
Sign up to set email alerts
|

The median effective concentration of propofol with different doses of esketamine during gastrointestinal endoscopy in elderly patients: A randomized controlled trial

Abstract: Aims Propofol may result in hypotension, bradycardia and loss of protective reflexes, especially in elderly patients, while esketamine, a N‐methyl‐D‐aspartate receptor antagonist, has analgesic, anaesthetic and sympathomimetic properties and is known to cause less cardiorespiratory depression. We hypothesized that esketamine may reduce the median effective concentration (EC50) of propofol and coadministration is less likely to produce hypotension during gastrointestinal endoscopy in elderly patients. Methods N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
62
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 38 publications
3
62
1
Order By: Relevance
“…Tristimania 0 (0%) 0 (0%) 0 (0%) 0 (0%) 1.000 [15] also reported the effectiveness of esketamine as an adjunct to propofol target-controlled infusion for gastrointestinal endoscopy in elderly patients. Eberl and colleagues found that this combination was also effective in Endoscopic retrograde cholangiopancreatography (ERCP).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Tristimania 0 (0%) 0 (0%) 0 (0%) 0 (0%) 1.000 [15] also reported the effectiveness of esketamine as an adjunct to propofol target-controlled infusion for gastrointestinal endoscopy in elderly patients. Eberl and colleagues found that this combination was also effective in Endoscopic retrograde cholangiopancreatography (ERCP).…”
Section: Discussionmentioning
confidence: 97%
“…This result showed the efficacy of the subanesthetic dose of esketamine–propofol combination during GI endoscopy sedation. Yang et al [ 15 ] also reported the effectiveness of esketamine as an adjunct to propofol target-controlled infusion for gastrointestinal endoscopy in elderly patients. Eberl and colleagues found that this combination was also effective in Endoscopic retrograde cholangiopancreatography (ERCP).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many patients could not tolerate a bronchoscopic procedure without sedation for anxiety and intense stimulation. While the frequently reported regimens include an opioid/propofol combination, other authors [ 26 , 27 ] have suggested that esketamine may be both safe and effective for short surgery. Although previous studies on the safety and validity of esketamine in bronchoscopy are scarce, several studies have demonstrated the effectiveness of ketamine in bronchoscopy, especially for pediatric patients [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%